Poverty, not the poor: How recent research changes our understanding of the causes of and policies for reducing systemically high poverty in the U.S. - David Brady (Luxembourg Income Study (LIS), 2023)
This review explains how and why the U.S. has systemically high poverty. Descriptive evidence shows U.S. poverty is: (a) a huge share of the population; (b) a perennial outlier among rich democracies; (c) staggeringly high for certain groups; (d) surprisingly high for those who "play by the rules"; and (e) pervasive across various groups and places. This review then discusses and critiques three prevailing approaches focused on the individual poor rather than the systemically high poverty: (i) behavioral explanations "fixing the poor"; (ii) emotive compassion "dramatizing the poor"; and (iii) cultural explanations both dramatizing and fixing the poor. The essay then reviews political explanations that emphasize: the essential role of social policy generosity, political choices to penalize risks, power resources of collective political actors, and institutions. This review demonstrates a long emerging, but ascending and warranted, shift away from individualistic explanations of the poor towards political explanations of poverty.
Keywords: 330